2007
DOI: 10.1111/j.1365-2311.2007.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition trade‐offs in the organisation of a Mediterranean ant assemblage

Abstract: 1. The organisation of an ant assemblage inhabiting an olive orchard in central Italy was analysed and patterns of dominance among ant species were described in order to assess (i) the relationship between thermal dependency and degree of behavioural dominance, and (ii) the relationship between dominance and discovery ability. 2. Activity patterns of the most abundant species on trees were examined in a sample of 120 trees during spring and summer. The degree of behavioural dominance and the ability of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 37 publications
0
69
2
Order By: Relevance
“…In addition, species that were subordinate did not discover baits faster than did dominant species. Similarly, Santini et al (2007) found no evidence for the discovery-dominance or the dominance-thermal tolerance tradeoff in a Mediterranean ant assemblage, though such tradeoffs likely promote coexistence in other Mediterranean ant assemblages 1998a). Fellers (1987) found evidence of the discovery-dominance tradeoff in other temperate forest ant communities.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, species that were subordinate did not discover baits faster than did dominant species. Similarly, Santini et al (2007) found no evidence for the discovery-dominance or the dominance-thermal tolerance tradeoff in a Mediterranean ant assemblage, though such tradeoffs likely promote coexistence in other Mediterranean ant assemblages 1998a). Fellers (1987) found evidence of the discovery-dominance tradeoff in other temperate forest ant communities.…”
Section: Discussionmentioning
confidence: 94%
“…Physical attributes of these stands may differ enough from older forests to reverse the effects of interactions. For example, temperature, which depends on successional stage, may regulate competitive interactions (Cerda´et al 1988, 1997, Santini et al 2007. Habitat complexity may also reduce competitive interactions (Petren and Case 1998, Gray et al 2000, so the greater cover of dead wood in 0-4-year-old stands may limit competitive interactions with F. aquilonia.…”
Section: Discussionmentioning
confidence: 99%
“…Ant aggressiveness was assessed by calculating a BDI based on Santini et al (2007). The number of times individual ants were dominant or subordinate was recorded for each pair of ant species that encountered each other.…”
Section: Ant Aggressivenessmentioning
confidence: 99%